Assessing biomedical research capacities in selected countries of Latin America: challenges, opportunities, and recommendations - Jorge A. Huete-Perez; Narayana Salvatierra (Frontiers in Research Metrics and Analytics, 2025)
Despite increasing scientific output, biomedical research in Latin America remains unevenly developed, particularly in countries that are often overlooked in regional science policy discussions. This study assesses research capacities in Colombia, Costa Rica, Guatemala, Panama, and Peru, identifying key challenges, opportunities, and strategies to strengthen the region's scientific landscape. Using a mixed-methods approach—including surveys, expert interviews, and data analysis—this study examines infrastructure, institutional support, funding mechanisms, researcher training, and international partnerships. Additionally, it evaluates the impact of global programs, such as the Pew Latin American Fellows Program, in advancing research capacity. Findings highlight substantial differences in national R&D investment, workforce development, and institutional capabilities. Colombia and Costa Rica exhibit more developed research ecosystems, while Guatemala, Panama, and Peru face constraints such as limited national funding, dependency on external grants, and gaps in PhD/postdoctoral training. However, emerging opportunities include specialization in key biomedical fields, notably infectious diseases, genomics, and biotechnology, strengthening global partnerships, and leveraging research networks to address Latin America's pressing health challenges. This study contributes to ongoing discussions on regional science policy and international collaboration by addressing knowledge gaps and providing evidence-based recommendations for research funding, institutional development, and workforce expansion. To foster long-term growth, it recommends increasing national R&D investment, modernizing research infrastructure, expanding doctoral and postdoctoral training, and strengthening institutional and global research partnerships. By implementing targeted policies and institutional strategies, Latin America can enhance its role in global biomedical research and innovation while addressing regional health priorities.